Chironomidae em diferentes ambientes da bacia do rio Ivinhema, planície de inundação do alto rio Paraná, MS. - Butakka, Cristina Márcia de Menezes (2005)
The first chapter of this work have objective to characterize the Chironomidae fauna in the basin of the Ivinhema River, in the main channel, in the secondary channel, in five lakes connected and in five lakes without connection and to analyze the numerical density, biomass, diversity and dominance of the larvae. Of the 68 taxa, Aedokritus sp., Tanytarsus sp., Chironomus gr. decorus sp. I and Procladius sp.1 were found in all sampling sites. Chironomus gr. decorus sp.1 contributed with the greatest biomass values in the central region of lakes without connection, whereas Aedokritus sp. dominated in the littoral region of lakes. The greater values of diversity indices of Chironomidae in the littoral region of channels whereas the dominance indices were greater on the central region of theses environments. In the second chapter was analyzed the diet of Chironomid larvae and calculated the relative abundance of dietary items using the area taken in the digestive content Chironomid larvae. The categories recorded were algae, organic detritus (fragments of algae, of plants and animals), mineral detritus (sponge spicules), and fungi spores. The most common algae were those of the class Bacillariophyceae (Aulacoseira granulata, Pinnularia sp.1, Fragilaria sp.1, Gomphonema gracile; Gomphonema parvulum, Navicula cf. constans, Eunotia bidens and Cymbella sp.1) and those of the class Euglenophyceae (Trachelomonas sp.2). The majority in the larvae appeared to be opportunistic and omnivore, feeding non-selectively from the available sources in each type of habitat. In the chapter III, was carried a study to analyze the niche overlap between trophic groups of Chironomid larvae in different types of environments. The greatest number of trophic niche overlaps was found between collectors-gatherers (Aedokritus sp., Chironomus gr. decorus I, Goeldichironomus neopictus) and other trophic groups in the connected lakes. In the chapter IV, to of examine the emergence of Chironomidae in the different habitats of the Patos Lake, were utilized traps of surface emergence (floating) for a period of 48 ±2 hours, obtaining quantitative data for richness and abundance. The taxons identified in the specific level were: Goeldichironomus neopictus, G. petiolicola, G. maculatus, Tanytarsus ligulatus, Parachironomus atroari, P. guarani e P. cayapo. The higher abundances were of Polypedilum (Tripodura) sp.1 and Tanytarsus ligulatus, specially in the littoral region. The spatial variation leads to the assumption that the attributes of the Chironomidae fauna vary with the diversity and quantity of habitats of the lakes, channels and rivers in the floodplain of the Upper Paraná River.